Factors influencing the achievement in mathematics of malay secondary school students - Che A. Halim Che Daud (Fakulti Pengurusan Ekonomi, 2010)
The present situation of many secondary school students having difficulty in learning mathematics needs to be thoroughly investigated. Various factors need to be studied in order to determine why these students failed to perform satisfactorily in mathematics. For this research, a group of three hundred secondary school students were studied in order to determine the influence of students' internal characteristics on achievements in mathematics. This research focused on the following seven internal characteristics: Attitudes towards mathematics, mathematics anxiety, motivation to study mathematics, personality and behavioural characteristics, cognitive readiness, learning strategies, and learning styles.